Child Marriage and Infant Mortality in Indonesia: A Spatial Analysis Approach - Suryaningrum, Nugrahayu; Samosir, Omas Bulan; Djutaharta, Triasih (Al-Sihah : The Public Health Science Journal, 2023)
Spatial analysis approach is capable of identifying spatial clustering of Infant Mortality Rate (IMR) across districts/cities in Indonesia. This information is essential for policymakers when developing appropriate health interventions at districts/cities level. At delivery, maternal age is one of the strongest predictors of infant mortality, which is closely related to child marriage. Therefore, this study aimed to determine the relationship between child marriage and IMR in Indonesia, which was controlled by the influence of maternal, household, and health factors. The results showed that there were spatial dependency on IMR in Indonesia. Analysis Regression Spatial Durbin Model showed that child marriage had a positive and significant relationship with IMR. Furthermore, it was discovered that IMR was influenced by several explanatory variables in districts and neighboring cities. To reduce mortality rate, there was a need to increase health services by developing neighboring areas and building access to areas with good health facilities. Educational initiatives are also important, emphasizing the importance of delaying the age of marriage and enforcing the minimum age limits. This approach empowered every child to marriage carefully and had good reproductive health knowledge that could decrease IMR in Indonesia.